(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
E-learning has lately grown into a proliferating area because of its good potentials for instructional and assessment purposes. Context of instruction where e-learning is commissioned can bear implications for the scope and instances of application. The present study addresses the major challenges faced in this respect by Iranian practitioners and also offer some practical solutions to these challenges. As a descriptive study in nature, the data population comprised 350 Iranian citizens from various social, economical and educational backgrounds aged between 16 and 53 who were asked to prioritize six major challenges Iranian people face regarding the e-learning arena on a standardized Likert-type scale. The challenges were selected from among those earlier cited in the related literature. Six major challenges to be prioritized were: lack of government support, lack of public awareness, high costs of e-learning, collectivist society of Iran, low-speed internet, internal filtering and external sanctions. The results indicated that lack of public awareness, lack of government support and collectivist society of Iran were chosen by the participants as the main hurdles in the path of e-learning development in Iran, respectively. Further solutions and implications of the study are discussed in the study.